1997
DOI: 10.1002/jlb.62.4.524
|View full text |Cite
|
Sign up to set email alerts
|

Increased monocyte TNF-α message stability contributes to trauma patients' increased TNF production

Abstract: Abstract:Post-trauma elevation of tumor necrosis factor a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…In conclusion, we show that systemic administration of ARA290 is highly effective in reducing burn wound expansion by preventing microvascular thrombosis and progressive necrosis, which correlated with a decrease in TNF-α secretion levels of innate immune cells, including several markers of related proinflammatory pathways in the wounds (37,38). The decrease in burn depth and area would likely reduce the necessity for extensive surgical debridement as well as secondary wound closure by means of skin grafting.…”
Section: Discussionmentioning
confidence: 63%
“…In conclusion, we show that systemic administration of ARA290 is highly effective in reducing burn wound expansion by preventing microvascular thrombosis and progressive necrosis, which correlated with a decrease in TNF-α secretion levels of innate immune cells, including several markers of related proinflammatory pathways in the wounds (37,38). The decrease in burn depth and area would likely reduce the necessity for extensive surgical debridement as well as secondary wound closure by means of skin grafting.…”
Section: Discussionmentioning
confidence: 63%
“…Increased circulating CD64 ϩ inflammatory Macs have been previously described in injury, and these more inflammatory Mac have altered function (41, 44 -46). We have previously reported that trauma patient M with high CD64 expression produce exaggerated amounts of the 26-kDa, cell-associated form of TNF-␣ with increased TNF-␣ mRNA stability (1,47). A recent report describes hM-CSF-differentiated PBMC Mac as producing higher TNF levels than M because of their increased TNF mRNA stability.…”
Section: Discussionmentioning
confidence: 98%
“…M any studies have demonstrated that monocyte (M ) 4 / macrophage (Mac) dysfunctions are pivotal in the development of the dysregulated inflammatory cytokine production typical of trauma patients who develop multiple organ failure and infectious complications (1)(2)(3)(4)(5)(6). Simultaneous with the often-exaggerated inflammatory response, these patients' M show depressed HLA-DR expression and a failure of Ag-presenting functions, which appears to be correlated with the development of T cell immunosuppression (7)(8)(9)(10)(11)(12)(13).…”
Section: M-csf Combined With Il-6 Inhibits M -To-idc Differentiation mentioning
confidence: 99%
“…Burn and trauma patients' MO accumulate large quantities of the membrane-associated form of TNF-␣ (mTNF-␣) while decreasing their secreted levels (7,8). Such postinjury increased MO TNF-␣ production is partially stimulated through the Toll-like receptors (TLR) by bacterial products and debris from damaged tissue (9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%
“…We previously showed that aberrant MO to dendritic cell (DC) differentiation correlates with increased multiple organ dysfunction posttrauma (6). Excessive production of membrane-associated TNF-␣ and other inflammatory monokines are another hallmark of postinjury MO pathology (7,8).…”
Section: Introductionmentioning
confidence: 99%